P45 Simulation following theory to embed learning on a critical care course. (3rd November 2019) - Elson, Ross; Nash, Abigail; Bradshaw, Jane; Kidd, Nicola
Abstract : Background: Nurses working in Critical Care areas must obtain a certain skillset, this is a requirement from the RCPCH (2014) and PICS (2015). Traditionally theory is delivered within a classroom environment and skills acquired through clinical practice. It is important that skills can be learnt and practiced in a safe environment through simulation. Our aim was to introduce simulation into our critical care course as part of a flipped classroom to build on the theory learnt in a practical way. Summary of work: In September 2018 we designed our Critical Care Course cardiovascular session around a flipped class model to allow more time for practical scenarios. Nurses utilise online education resources prior to entering a two-hour theory session. During this session knowledge is built on the pre-session work and nurses are prepared with the theory required for cardiac scenarios such as SVT, Sinus bradycardia and cardiac arrest. Specific learning outcomes are set for each scenario for example administration of adenosine or safe cardioversion with the defibrillator. Further learning is consolidated during a supportive teaching debrief. Summary of results: We have delivered 3 courses so far in this way. 55 nurses from 8 hospitals attended the session, from 21 different ward areas Feedback was obtained using post session questionnaire to establish the usefulness of the session to their practice. 80% (n=44) of nurses completed the feedback. 91% (n=40) found the scenarios useful in embedding the theory taught. 9% (n=4) found the group size to be too large which impacted on their experience. Changes were made following this result in September, and since then the results have improved. Nurses attending the session said they found the session interesting and enjoyable, they liked putting the theory into practice and found the scenarios really helpful. Following the course nurses have reported that they now feel more confident in dealing with similar situations in practice. Conclusion: A learning environment that uses Simulation following theory allows nurses to safely develop the skills required work in a Critical Care environment. This has shown to be an enjoyable and effective method of adult learning. Reference: RCPCH: Back to Facing the Future 2014 http://www.rcpch.ac.uk/system/files/protected/news/Back%20to%20Facing%20the%20 Future%20FINAL_1.pdf The Paediatric Intensive Care Society. Standards for the care of critically ill children. [4th Edition]. 2015. http://www.ukpics.org.uk/documents/PICS_standards.pdf